2004
DOI: 10.1038/oby.2004.185
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dimorphism and Regulation of Resistin, Adiponectin, and Leptin Expression in the Mouse

Abstract: GUI, YAOTING, JOSEF V. SILHA, AND LIAM J. MURPHY. Sexual dimorphism and regulation of resistin, adiponectin, and leptin expression in the mouse. Obes Res. 2004;12:1481-1491. Objective: To examine gender differences and hormonal regulation of resistin, adiponectin, and leptin. Research Methods and Procedures: Plasma levels were measured, and mRNA expression in perigonadal fat was quantified by RNase protection assays. Results: Plasma resistin declined with age despite an increase in adiposity in both genders. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
104
2
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(125 citation statements)
references
References 37 publications
17
104
2
2
Order By: Relevance
“…However, in agreement with most (38, 39), but not all (37) reports, we found no correlation of resistin with sex steroids or BMI. This lack of correlation is consistent with results from animal studies where estradiol did not modify plasma resistin levels (40). However, the fact that resistin levels are their highest in adult females and correlate with the leptin/receptor ratio, which does not occur in males, suggests a possible link between resistin levels and female body fat content changes.…”
Section: Discussionsupporting
confidence: 78%
“…However, in agreement with most (38, 39), but not all (37) reports, we found no correlation of resistin with sex steroids or BMI. This lack of correlation is consistent with results from animal studies where estradiol did not modify plasma resistin levels (40). However, the fact that resistin levels are their highest in adult females and correlate with the leptin/receptor ratio, which does not occur in males, suggests a possible link between resistin levels and female body fat content changes.…”
Section: Discussionsupporting
confidence: 78%
“…Nevertheless, the mechanisms that underlie the regulatory effect of testosterone on adiponectin production are still poorly understood. Neither castration nor testosterone interferes with the mRNA abundance of the adiponectin gene in adipocytes (27,34), although these treatments modulate the serum levels of total adiponectin, suggesting that the regulation occurs at a posttranscriptional level. In this study we provide both experimental and clinical evidence demonstrating that testosterone exerts its regulatory actions at the level of adiponectin oligomeric complex distribution.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that a certain degree of sexual dimorphism exists in the regulation of APN expression under non-stress conditions. For example, serum APN levels are increased by aging in female, but not male, mice [19]. In addition, the changes in cytokine production caused by LPS-induced sepsis have also been reported to exhibit sexual dimorphism [27].…”
Section: Effects Of Lps Injection On the Hypothalamic Mrna Expressionmentioning
confidence: 99%
“…Furthermore, the changes in hypothalamic AdipoR and subcutaneous APN mRNA levels induced under septic conditions also remain to be investigated. As it has been suggested that basal adiponectin levels exhibit a certain degree of sexual dimorphism [19], we speculate that the changes in the expression levels of adiponectin and its receptors induced in response to acute inflammatory conditions might also differ between the sexes. Accordingly, the present study evaluated the changes in APN and AdipoR expression at the peripheral and central levels; i.e., their serum, WAT, hepatic, and hypothalamic levels, under LPS-induced septic conditions in female rats.…”
Section: Effects Of Lps Injection On the Circulating Levels Of Adiponmentioning
confidence: 99%
See 1 more Smart Citation